In vitro and in vivo evaluation of nano-based films for buccal delivery of zolpidem - Bandar Essa AL-DHUBIAB
Abstract Insomnia is becoming increasingly prevalent in the world general population. Therapies used by patients include over-the-counter therapies, herbal and dietary supplements, and pharmacological or nonpharmacological treatments. Among these, zolpidem is a pharmacological treatment popularly used for insomnia. Zolpidem is well tolerated and especially efficacious for initiation of sleep, and therefore is effective for the treatment of sleep-onset insomnia. The purpose of the present study was to design and evaluate zolpidem nanoparticle-impregnated buccal films to prolong the duration of its action. Zolpidem nanospheres were prepared by double emulsion solvent evaporation and then loaded into buccoadhesive films (Z1-Z4) comprised of different concentrations of HPMC K100, Eudragit® RL 100, and carbopol 974P. The prepared films were characterized for physicomechanical properties, mucoadhesion, percent hydration, in vitro drug release, ex vivo permeation, and in vivo studies. In vitro drug release was found to depend upon film composition. Ex vivo studies showed that film Z4 had the highest flux. In vivo studies revealed that administration of zolpidem nanosphere-impregnated film enhanced absorption of the drug (p < 0.0001), with a higher peak plasma concentration (52.54 ± 8.22 ng/mL) and area under the curve from time 0 to α (236.00 ± 39.51 ng.h/mL) than oral administration. The increase in time taken to reach the maximum drug concentration (1.5 h) further signifies the potential of these films to provide prolonged drug release. Given these promising results, we concluded that these buccal films could be an alternative route for effective zolpidem delivery.